Perceptions of International Business Students on Presidential Rhetoric in Latin America - Guerrero, Lugo Manuel Barbosa; Rozo, Jairo Jamith Palacios; Cocunubo, Iván Fernando Amaya (Journal of Ecohumanism, 2024)
This study analyzes the perceptions of International Business students regarding presidential discourses in Latin America, with particular emphasis on narratives related to security and democratic governance. A Likert-type survey was applied to 128 students, assessing seven dimensions associated with political orientation, security rhetoric, and international perceptions of governance. The results indicate that participants perceive presidential speeches as prioritizing security over governance, especially during periods of crisis. Likewise, a strong perception was identified regarding the influence of political orientation on the discursive management of security, as well as a positive evaluation of the impact of these speeches on the international image of the countries. The study contributes to understanding the role of political communication in legitimizing security strategies in Latin America.